Rethinking AI literacy: How high school students navigate ChatGPT in English language learning - Hasanah, Farah Faridatul; Degeng, Putu Dian Danayanti (Englisia Journal, 2025)
This study explores high school students’ AI literacy and their use of ChatGPT in English language learning, addressing the gap in AI application research at the secondary education level. Utilizing an explanatory sequential mixed-methods design, the study evaluated the AI literacy of 100 high school students via a validated questionnaire, assessing affective, behavioral, cognitive, and ethical dimensions. Follow-up interviews with six students of varying AI literacy levels provided deeper insights into their experiences and perceptions of ChatGPT. Findings indicate positive attitudes toward ChatGPT, with high scorers demonstrating robust engagement, adaptability, and ethical awareness in using the tool for English learning. Conversely, low scorers showed limited understanding, over-reliance on ChatGPT for superficial tasks, and underutilization of its potential for deeper learning. Despite its benefits, concerns about over-reliance and ethical issues highlight the need for structured guidance. Variations in AI literacy emphasize the importance of targeted interventions to promote critical thinking and responsible AI use. This study offers practical recommendations for integrating AI literacy into curricula to ensure effective and ethical use of AI tools. Future research should investigate the impact of comprehensive AI literacy programs on student engagement and learning outcomes.